National Legislative and Regulatory Activities (OECD Publishing, 2008)
Belarus Act on the Use of Atomic Energy (2008) France Safety guideline on final disposal of radioactive waste in a deep geological repository (2008) Decree concerning the procedures applicable to foreign spent nuclear fuel and radioactive waste reprocessing (2008) Germany Amendment to the 1986 Act on Preventive Protection of the Public Against Radiation (2008) Order on the International Carriage of Dangerous Goods by Rail (2008) Act on the 2004 Protocols to Amend the Paris Convention and the Brussels Supplementary Convention; Act to Amend the Atomic Energy Act (2008) Hungary Energy Policy 2007-2020 Framework Strategy (2008) Indonesia Regulation on licensing of uses of ionizing radiation sources and nuclear materials (2008) Italy Implementing law on urgent provisions for economic development etc. (2008) Montenegro Law on the Environment (2008) Romania Decision on the organisational structure of the Nuclear Agency (2008) Decision on the selection of the investors of Units 3 and 4 of Cernavoda NPP (2008)Consolidated version the Civil Protection Law (2008) National strategy for preventing emergency situations (2008) National strategy for information sharing and communication in the event of an emergency (2008) Russian Federation Decree transferring responsibilities to the Ministry of Natural Resources and Ecology (2008) Slovak Republic Transposition of Council Directive 2006/117/Euratom (2008) Ukraine Decree creating the state enterprise "Nuclear Fuel" (2008) Amendment to the law on radioactive waste management (2008) United Kingdom New Ministry for Energy and Climate Change (2008) United States Next generation nuclear plant licensing strategy (2008) Public health and environmental radiation protection standards for Yucca Mountain, Nevada (2008) Inflation adjustment to the Price-Anderson Act (2008)